Senile Lemierre syndrome complicated with descending necrotizing mediastinitis: A case report. Issue 35 (August 2018) - Yang, Xu; Yang, Yi-Fei; Zhu, Zhi-Chao; Xu, Tian-Shu; Cheng, Yi-Nan; Sun, Zhao-Yao
Abstract: Rationale: Senile patients with LS complicated with DNM are rarely seen in clinical practice, and extensive cervical incision and drainage plus administration of effective antibiotics are the basis for treatment. Currently, the treatment controversy mainly has focused on whether mediastinal incision and drainage is necessary for patients with type I DNM, and whether anticoagulation therapy is required for jugular venous emboli and distant metastatic emboli induced by LS. Patient concerns: A female, 76 years old, developed pain of tonsil on right side 5 days ago, and felt that the pain aggravated complicated with dysphagia and swelling pain of neck on both sides since then. Diagnoses: She was diagnosed with LS complicated with type I DNM. Interventions: Tazobactam and Piperacillin 4.5 q8h and Ornidazole 100 ml q6h ivgtt were administered empirically, and secondary extensive cervical incision and drainage was performed under general anesthesia, after which low molecular weight heparin 4250 U q12h SC was administered. G test was performed 3 days later, which showed (1, 3)-β-D-glucan >1000 pg/ml. Bridging anticoagulation therapy, low molecular weight heparin 4250 U q12h SC, and Warfarin 2.5 mg qd po were given one week later. Low molecular weight heparin SC was discontinued and only Warfarin po was administered after treatment of bridging therapy for 3 days. Outcomes: CT of head and neck was reexamined on post-admission d24 and revealed that neck infection was improved on both sides, jugular vein distension on right side was restored to normal, abscess and pneumatosis of superior mediastinum were improved, distension of pulmonary artery on both sides was normalized, WBC was 9.94×109/L, neutrophil count was 4.43×109/L, CRP level was 9.8mg/L, D-D level was 0.81mg/L, PCT level was 0.800ng/mL and G test suggested (1, 3)-β-D-glucan pf 27.1 pg/mL. Lessons: Concomitant use of anticoagulants on the basis of repeated cervical incision and drainage + administration of effective antibiotics can obtain excellent therapeutic efficacy in the treatment of patient with LS complicated with type I DNM.